Effects of hydrogen sulfide on the early developmental stages of Javanese carp, Puntius gonionotus (Bleeker) - Md. Yusoff, Fatimah; Law, Ah Theem; Teo, Hui Yoong; Hoque, M. T. (Asian Fisheries Society, 1998)
The toxicity of hydrogen sulfide (H2S) to the larvae and eggs of the Javanese carp, Puntius gonionotus (Cyprinidae) was determined using a flow-through bioassay. The eggs and larvae showed similar low tolerances to H2S. The EC50 value for the eggs was 2.8 µg l-1 H2S. One hundred percent of the eggs failed to hatch at H2S levels higher than 3.4 µg l-1 H2S, while a 100% mortality of the larvae occurred at 5.4 µg l-1 H2S. The growth rate of the larvae exposed to H2S level higher than 0.6 µg l-1 was significantly reduced. Newly hatched larvae from eggs exposed to more than 0.6 µg l-1 H2S showed tail deformities. Histological studies showed increasing degrees of hyperplasia in fish gills at increasing H2S concentrations. This study indicates that P. gonionotus is vulnerable to organic pollution in the aquatic environment.